Temperature profile of moving belt with direct IR heating using CFD modelling - P Vichaiya; J S Jongyingcharoen (My University, 2019)
Abstract Radiation heat transfer requires no medium, so energy lost is minimal. Infrared wave band is used for heating. However, radiative heating has limitation on the penetration depth. It infiltrated only a few millimetres into an object. IR drying can be used for thin layer drying. Continuous IR drying was an ideal process to use in drying. A pilot continuous IR drying tunnel was constructed. CFD model was used to generate the image of temperature profile of a moving belt which no other mean of temperature measurement can be pursued. The model was compared to measuring points for validation. The result was fair. By varying the IR heating power and speed of the belt, many scenarios can be used to find the optimum condition for drying.
Keywords: Radiant energy; Radiant heat; Thermal Radiation; Penetration (warfare); Radiant heating; Infrared heater; Thermal Analysis in Power Transmission